Raising concerns on questionable ethics approvals – a case study of 456 trials from the Institut Hospitalo-Universitaire Méditerranée Infection - Fabrice Frank; Nans Florens; Gideon Meyerowitz-katz; Jérôme Barriere; Éric Billy; Véronique Saada; Alexander Samuel; Jacques Robert; Lonni Besançon (Research Integrity and Peer Review)
Abstract Background The practice of clinical research is strictly regulated by law. During submission and review processes, compliance of such research with the laws enforced in the country where it was conducted is not always correctly filled in by the authors or verified by the editors. Here, we report a case of a single institution for which one may find hundreds of publications with seemingly relevant ethical concerns, along with 10 months of follow-up through contacts with the editors of these articles. We thus argue for a stricter control of ethical authorization by scientific editors and we call on publishers to cooperate to this end. Methods We present an investigation of the ethics and legal aspects of 456 studies published by the IHU-MI (Institut Hospitalo-Universitaire Méditerranée Infection) in Marseille, France. Results We identified a wide range of issues with the stated research authorization and ethics of the published studies with respect to the Institutional Review Board and the approval presented. Among the studies investigated, 248 were conducted with the same ethics approval number, even though the subjects, samples, and countries of investigation were different. Thirty-nine (39) did not even contain a reference to the ethics approval number while they present research on human beings. We thus contacted the journals that published these articles and provide their responses to our concerns. It should be noted that, since our investigation and reporting to journals, PLOS has issued expressions of concerns for several publications we analyze here. Conclusion This case presents an investigation of the veracity of ethical approval, and more than 10 months of follow-up by independent researchers. We call for stricter control and cooperation in handling of these cases, including editorial requirement to upload ethical approval documents, guidelines from COPE to address such ethical concerns, and transparent editorial policies and timelines to answer such concerns. All supplementary materials are available.